Harmful or helpful? Trust in the police after a shock: a test of (dual) expectancy disconfirmation theory - Roché, Sebastian (Policing and society, 2025)
Can social and economic macro-social shocks significantly affect citizens’ trust in the police? We explore the credibility of dual expectancy disconfirmation theory whereby the trust in the police is the result of the responsibility attributed to the government for a shock combined with the evaluation of police action as helpful vs. harmful during the following crisis. Based on European Social Survey (ESS) data, we compare countries under shock with the rest of the EU states (Greece: economic hardship; France: terrorism; Spain: elite conflict. We show that, after a shock, trust in the police evolves as a result of a combined (dual)assessment of the government and the police by the citizens. Firstly, when a government is clearly responsible for the shock, it takes the blame, which spills over to the police. Conversely, when a government is confronted by a shock outside its decision-making realm, no blame spills over to the police. Secondly, the positive evaluation of the police depends on whether their intervention corresponds to the protective role they have been assigned: they are evaluated positively when they tackle a threat, and negatively when they forcibly prevent citizens from exercising their political rights. Thirdly, differential effects are always observable: segments of society which are exposed to more harm from the police become more reluctant to trust the police. This paper presents a theoretical backing for those studies that have previously dealt with shocks but were mostly based on micro level theories of police-citizens interactions with only limited theoretical attempts to consider the macro-level context.